L'antòleg com a crític: Versions de l'anglès (1938), Poesia anglesa i nord-americana (1955), i El gran vent i les heures (1983) de Marià Manent. - GRANELL SALES, CARLES (Scripta)
Marià Manent, mainly known for being a poet, translator, critic, and memorialist, was also an anthologist, a trait usually ignored. Besides the possibility of analysing his anthologies as collections of translations, the selection of the materials also shows his critical preferences. Taking into account that the selection of the works to be included in an anthology is a critical process, Manent's choices obey to a key principle of his poetics, that is, the conception of literature as a creative process which takes part into tradition, benefits from it, and transforms it. The comparative method - especially displayed in his critical writings - was assumed and Manent made it the fulcrum of his critical procedures. Thus, his first published anthology of translations to Catalan Versions de l'anglès (1938) and its second edition retitled El gran vent i les heures (1983) prove the continuity, consistency and coherence of this central aspect of his poetics, remarkably in the representation of imagery. The anthology Poesia anglesa i nordamericana (1955) also echoes recurrent imagery in poems, but Manent's critical participation is more evident in the introductory notes to each author. In these the critic-anthologist offers comparative observations and an implicit defense of the Catholic tradition.